Comprehensive characterization of plasma cell-free Echinococcus spp. DNA in echinococcosis patients using ultra-high-throughput sequencing. - Jingkai Ji; Bin Li; Jingzhong Li; Wangmu Danzeng; Jiandong Li; Yanping Zhao; Gezhen Qiangba; Qingda Zhang; Nibu Renzhen; Zhuoga Basang; Changlin Jia; Quzhen Gongsang; et al. (Public Library of Science (PLoS), 2020)
BACKGROUND:Echinococcosis is a life-threatening parasitic disease caused by Echinococcus spp. tapeworms with over one million people affected globally at any time. The Echinococcus spp. tapeworms in the human body release DNA to the circulatory system, which can be a biomarker for echinococcosis. Cell-free DNA (cfDNA) is widely used in medical research and has been applied in various clinical settings. As for echinococcosis, several PCR-based tests had been trialed to detect cell-free Echinococcus spp. DNA in plasma or serum, but the sensitivity was about 20% to 25%. Low sensitivity of PCR-based methods might be related to our limited understanding of the features of cell-free Echinococcus spp. DNA in plasma, including its concentration, fragment pattern and release source. In this study, we applied ultra-high-throughput sequencing to comprehensively investigate the characteristics of cell-free Echinococcus spp. DNA in plasma of echinococcosis patients. METHODOLOGY/PRINCIPAL FINDINGS:We collected plasma samples from 23 echinococcosis patients. Total plasma cfDNA was extracted and sequenced with a high-throughput sequencing platform. An average of 282 million read pairs were obtained for each plasma sample. Sequencing data were analyzed with bioinformatics workflow combined with Echinococcus spp. sequence database. After identification of cell-free Echinococcus spp. reads, we found that the cell-free Echinococcus spp. reads accounted for 1.8e-5 to 4.0e-9 of the total clean reads. Comparing fragment length distribution of cfDNA between Echinococcus spp. and humans showed that cell-free Echinococcus spp. DNA of cystic echinococcosis (CE) had a broad length range, while that of alveolar echinococcosis (AE) had an obvious peak at about 135 bp. We found that most of the cell-free Echinococcus spp. DNA reads were from the nuclear genome with an even distribution, which might indicate a random release pattern of cell-free Echinococcus spp. DNA. CONCLUSIONS/SIGNIFICANCE:With ultra-high-throughput sequencing technology, we analyzed the concentration, fragment length, release source, and other characteristics of cell-free Echinococcus spp. DNA in the plasma of echinococcosis patients. A better understanding of the characteristics of cell-free Echinococcus spp. DNA in plasma may facilitate their future application as a biomarker for diagnosis.